1992
DOI: 10.2307/1941856
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives for Sustainable Natural Resources Management

Abstract: The USDA Forest Service is taking a new direction in its research and management programs in response to changing views of land and natural resources. The changes reflect the complexity of society's concerns and expectations for national forest ma?agement, including biological diversity, ecological function and balance, product yields, soctal values, and the beauty and integrity of natural environments. The new direction involves a shift in management focus from sustaining yields of competing resource outputs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(98 citation statements)
references
References 8 publications
0
94
0
3
Order By: Relevance
“…This factor shows a high support for ideas including biological diversity, ecological function and balance, product yields, social values, and the beauty and integrity of natural environments. This perspective of utilitarian values includes a reemergence of earlier philosophical themes of maintenance of nature's balance, resource development without waste, and protection and restoration of the beauty of natural environments (Glacken, 1956) with a goal of sustaining the health, diversity, and productivity of land to serve the needs of this and future generations (Kessler, Salwasser, Cartwright, & Caplan, 1992), which were identified as high-ranking statements in Table 1. This factor also shows strong disagreement with the notions of ecological ignorance and a mechanistic, reductionist worldview, which represent the traditional values of conservatism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This factor shows a high support for ideas including biological diversity, ecological function and balance, product yields, social values, and the beauty and integrity of natural environments. This perspective of utilitarian values includes a reemergence of earlier philosophical themes of maintenance of nature's balance, resource development without waste, and protection and restoration of the beauty of natural environments (Glacken, 1956) with a goal of sustaining the health, diversity, and productivity of land to serve the needs of this and future generations (Kessler, Salwasser, Cartwright, & Caplan, 1992), which were identified as high-ranking statements in Table 1. This factor also shows strong disagreement with the notions of ecological ignorance and a mechanistic, reductionist worldview, which represent the traditional values of conservatism.…”
Section: Discussionmentioning
confidence: 99%
“…This factor also shows strong disagreement with the notions of ecological ignorance and a mechanistic, reductionist worldview, which represent the traditional values of conservatism. These values can be summarized as seeing land primarily in terms of its capability to yield desired goods, identifying factors that limit production, the major objective of management is to remove or reduce those limitations, and relationships among different resources were treated and thought of as constraints on the dominant use (Kessler et al, 1992), all of which were identified in low ranking statements in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ostrom [29] determines that collective management strengthens consumers capacities, to achieve a sustainable management [21]. Thus, this discussion is marked by a "good governance" to promote efficiency and enhance sustainability [30]. The public policy, therefore, requires to involve the actors who participate in it [31], in this way, we try to correct the deficiencies in the management caused by the non-participatory policy [32].…”
Section: Collective Water Magamentmentioning
confidence: 99%
“…Recently, the value of maintaining species habitats and forest health ( e g , resistance from fire and insect outbreaks) has been reemphasized. Great strides have been made in recognizing the ecological values of forests and in communicating to public and private owners how to preserve these values (Swanson and Franklin 1992, National Research Council 1992, Salwasser 1990, Kessler et al 1992, Franklin 1989). Yet there are still gaps.…”
Section: Attributes Of Forests That People Valuementioning
confidence: 99%